Aspectos de controladoria em uma farmácia escola de uma Instituição de Ensino Superior Pública - Marques, Pauliane Venessa da Silva (2023)
The School Pharmacy is a health establishment linked to a higher education institution that presents itself as a scenario of teaching practice, research and extension for students in the area of pharmacy and works with the community by providing pharmaceutical services such as dispensing and handling of medicines, pharmaceutical assistance, among others. This case study, descriptive in nature, with a quanti-qualitative approach, has as its general objective to analyze the activities performed in the School Pharmacy of a Public Higher Education Institution in the scope of the Controllership. As a theoretical foundation for the research, themes about School Pharmacy and Controllership will be addressed. The methodology applied for data collection was carried out through the analysis of documents, direct observation of the activities carried out in the School Pharmacy and a structured questionnaire applied to servers. For the quantitative analysis, data were tabulated in an electronic spreadsheet and classical methods of descriptive statistics were applied, while, for the qualitative analysis, an interpretative analysis was carried out with the answers of the research participants. The results obtained pointed to an unsatisfactory execution of the activities and functions of the Controllership, addressed in this research, with the exception of the control function that reached a general average of 2.98, being classified in the category as satisfactory execution. Improvements were suggested for the organizational management of the School Pharmacy, in light of the Controllership, by means of the respondent’s reports about what could be implemented for a better organizational management. It is concluded, therefore, the importance of the Controllership along with its activities, functions and tools for a good management of the School Pharmacy.